Cognitive dysfunction 1 year after COVID‐19: evidence from eye tracking. Issue 11 (20th October 2022) - Carbone, Federico; Zamarian, Laura; Rass, Verena; Bair, Stefanie; Ritter, Marcel; Beer, Ronny; Mahlknecht, Philipp; Heim, Beatrice; Limmert, Victoria; Peball, Marina; Ellmerer, Philipp; Schiefecker, Alois Josef; et al.
Abstract: Increasing evidence suggests persistent cognitive dysfunction after COVID‐19. In this cross‐sectional study, frontal lobe function was assessed 12 months after the acute phase of the disease, using tailored eye tracking assessments. Individuals who recovered from COVID‐19 made significantly more errors in all eye tracking tasks compared to age/sex‐matched healthy controls. Furthermore, patients who were treated as inpatients performed worse compared to outpatients and controls. Our results show impaired inhibitory cortical control in individuals who recovered from COVID‐19. The association between disease severity and its sequelae may contribute to a better understanding of post‐COVID‐19 cognitive function.